Rethinking educational practice through reflexive inquiry essays in honour of susan groundwater-smith - SpringerLink (Online Service). (Dordrecht Springer Netherlands Imprint: Springer, 2011)
Rethinking Education Practice Through Reflexive Inquiry is a compilation of essays that explore contemporary issues in practitioner inquiry and action research from the perspective of both university-based and school-based authors. The essays discuss the practical, political and theoretical dimensions of practitioner inquiry, advancing the argument that the adoption of an inquiring approach to practice is both an integral dimension of teachers? work in the modern school as well as critical to effective and authentic professional learning. And the essays draw on the work of Groundwater-Smith to demonstrate the benefits brought to bear on schools, teachers and learners when the complex nature of the relationship between inquiry and practice is understood and acted upon in pursuit of democratic knowledge interests.
Electronic reproduction.
Keywords: Teaching; Teachers -- Training of; Electronic books